Delirium and Dementia in Hospitalized Older Adults: Differential Diagnosis, Screening, Management, Rehabilitation and Quality of Care - Mąka, Magdalena; Woźniak, Julia; Kadłubek, Sabina; Kapturska, Natalia; Kardaszewski, Piotr; Cymerys, Kinga; Kalinowski, Szymon; Sikora, Dominik; Kamiński, Jakub; Góralczyk, Ewa (Quality in Sport, 2026)
Introduction: Delirium and dementia are among the most common neurocognitive disorders in hospitalized older adults. As populations age, both conditions are becoming a major challenge for healthcare systems. Recent evidence suggests that their relationship is more complex than previously thought, with important implications for diagnosis, prevention, and long-term outcomes. Purpose of Research: This review summarizes current knowledge on the relationship between delirium and dementia in older adults, with emphasis on risk factors, diagnostic difficulties, prevention, treatment, rehabilitation, and long-term cognitive consequences. Material and methods: A literature review was conducted using publications identified in Google Scholar, PubMed, and Embase. The selected studies focused on delirium and dementia in hospitalized older adults, including epidemiology, diagnosis, prevention, management, and cognitive outcomes. State of knowledge: Delirium remains one of the most common complications of hospitalization in older adults and is still underrecognized, especially in patients with pre-existing dementia. Distinguishing acute delirium from chronic cognitive decline is difficult but essential. Current evidence shows that delirium is associated with longer hospitalization, functional decline, and worse long-term cognitive outcomes. Multicomponent non-pharmacological interventions, such as orientation support, early mobilization, hydration and nutrition optimization, and medication review, appear to be the most effective preventive strategy. More attention is also being paid to rehabilitation and follow-up after discharge. Conclusions: Delirium and dementia are closely interconnected and often coexist in hospitalized older adults. Early recognition, prevention, multidisciplinary management, rehabilitation, and appropriate follow-up are essential to improve outcomes and preserve cognitive function.